Importance of making cattle hornless using mechanical and genetical options - Mandal, D K (Indian Farming, 2015)
Dehorning is an age old, simple and cost-effective management practice that adds values to cattle rearing. With the growing awareness on animal welfare issues traditional painful methods of animal dehorning seems to be questionable. Local anesthesia prior to dehorning and post operative care under veterinary supervision is needed to be emphasized in dehorning practices. Early age dehorning/disbudding is more beneficial and less painful then older age. Little dehorning stress at an early age can be a great relief from severe pains of broken matured horn /horn cancer in future. Besides, dehorning facilitates easy handling, mechanized and modernized dairy/bull farm operations with less risk to both man and animals. In the coming years livestock farming by corporate sectors, increase in mechanization/ modernization would seek for well trained manpower specialized in horn and hoof care. Genetical approach is more humane towards hornless cattle production permanently and more cost-effective, once established. At present, it is more successful in beef industry and efforts are under way for dairy cows.